BERMAIN DRAMA MELALUI PEMBELAJARAN ROTATING ROLES - Mustakim Sagita Muhammad Iqbal (Jurnal Sosial Humaniora Sigli, 2020)
Drama is a form of literary work that has a part to be played by an actor, containing imitations of portraits of human life projected into a show. Playing drama is an activity to portray the characters in the story. In playing a drama, a player must be able to imagine the setting and actions of the actor and can use the voice in accordance with understanding of the feelings and thoughts of the actor. rotating roles is an active learning technique that provides opportunities for students to learn by practicing skills through characterization of characters or plays about certain situations in real life.This research is a classroom action research conducted in two cycles. Each cycle consists of four stages, namely: (1) planning, (2) implementation, (3) observation, and (4) reflection. This research was carried out collaboratively between researchers and English teachers. The subject of this study was high school level students in Pidie district and the object of this research was the students' playing skills using the rotating roles technique. Data collection is obtained through observation, field notes, practice tests playing drama, and interviews. The instruments used are field notes, observation sheets, questionnaires, and assessment sheets. Data analysis was carried out with qualitative descriptive techniques supported by quantitative data. The validity of the data is obtained through validity, namely democratic validity, results validity, process validity and dialogic validity, to achieve data reliability by presenting original data from the research results, such as field notes and interview transcripts. Keywords: Drama, rotating roles, speaking ability.